The Future of Warfare - Alexander, Bevin (Rawalpindi, Pakistan Army Education Press, 2000)
What are the strengths of our armed forces, and how can we best use them? What will future conflicts be like, and who will succeed? When should we intervene in military situations, and when should we remain neutral? Bevin Alexander answers these questions and more by discussing the nature of U.S. military policy (including the restraints imposed by our democratic traditions), and by examining the future makeup of the U.S. forces. Finally, he analyzes campaigns of the recent past - including the Korean, Vietnam, and Gulf wars - to show how troop mobility and guerrilla tactics have assumed paramount importance in military strategy. Alexander's argument, based on clear-eyed analysis and careful extrapolations from past successes and failures, is a blueprint for American policy. In the post-Cold War period, we must fight only those battles in which our ends can be achieved quickly and effectively.
Include Index and Bibliography
Keywords: Military policy -- United States -- Guerrilla warfare